THE IMPACT OF STUDENTS’ INTEREST IN ENGLISH SONGS ON THEIR LISTENING SKILLS - Farahtu Ayu Sapitri; Suryadi (STKIP Citra Bakti, 2023)
The influence of interest in English songs on students' listening skills at SMPN 1 Ciomas is the topic of this research. The goal of this study is to examine the impact that students' interest in English music has on their listening abilities in SMPN 1 Ciomas. This study is based on Slameto's (2010) theory that learning is more effective when it relates to students' interests. In order to analyze a specific population or sample for this study, the author employs a quantitative approach. Data are collected using research instruments, and data processing focus on quantitative/statistical analysis to test the hypotheses that have been set. Tests and questionnaires are employed as research tools. The population of this research is the students in SMPN 1 Ciomas, and the sample is the twelve grader students as many as 31 students. The data is analyzed using regression-correlation analysis. According to the study's findings, listening abilities and interest in English music are significantly positively correlated. Interest in English music has a 71.1% impact on listening abilities. In conclusion, persons who enjoy listening to English music engage in activities related to such songs on a regular basis, enjoying the good feelings that come along with them while also learning new things. This information aids listeners in comprehending what they are hearing. Additionally, since people's attention is enhanced by personal interest, which makes listening more effective, this interest also aids in the listening process.